2005
DOI: 10.2105/ajph.2004.050112
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in US Workers: The National Health Interview Survey, 1986 to 2002

Abstract: Weight loss intervention programs targeting workers employed in occupational groups with high or increasing rates of obesity are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
129
3
10

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(153 citation statements)
references
References 40 publications
11
129
3
10
Order By: Relevance
“…The prevalence of obesity was much lower in fire departments having a good WEFIT program than in fire departments without a WEFIT program: 25.3 versus 35.6 % by BMI . The prevalence of combined overweight and obesity was lower among female firefighters than among male firefighters, which is consistent with the previous studies (Caban et al 2005;Jahnke et al 2012). Future studies are needed to explore the reasons for the gender difference.…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
See 3 more Smart Citations
“…The prevalence of obesity was much lower in fire departments having a good WEFIT program than in fire departments without a WEFIT program: 25.3 versus 35.6 % by BMI . The prevalence of combined overweight and obesity was lower among female firefighters than among male firefighters, which is consistent with the previous studies (Caban et al 2005;Jahnke et al 2012). Future studies are needed to explore the reasons for the gender difference.…”
Section: Comparison With Previous Studiessupporting
confidence: 92%
“…The prevalence of obesity in the working population of the USA as in the general population has increased, particularly over the last three decades (Caban et al 2005). Male firefighters are among the top three occupational groups with the highest obesity prevalence in the USA (Caban et al 2005;Choi et al 2011;Haddock et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with Caban et al data that showed a higher prevalence of obesity in health service personnel and lower in healthdiagnosing occupations, also in the US. 8 Another interesting finding was that after adjusting for age, sex and occupation, no difference was found between study places. Homogeneity between study places reinforces the consistency of the study and leads us to speculate that the mix of obesity determinants should be the same.…”
Section: Discussionmentioning
confidence: 92%